The legal essence of tender under the legislation of the Republic of Kazakhstan - Zhagalov, R.B.; Akimzhanova, M.T. (Bulletin of the Karaganda University “Law Series”, 2024)
In modern conditions, tenders are a key source of income for government organizations and the business community, as it contributes to the effective organization of the procurement process and ensures transparen-cy and competitiveness in choosing a supplier. The authors of the article analyzed the key legislative acts regulating tenders, including the Law «On Public Procurement « in order to define the legal essence of the concept of «tender». As the analysis of industry legislation has shown, the concepts of «tender» and «contest» in most cases are identified and used as synonyms in the works of domestic and Russian scientists. The article also includes a comparative analysis with international practice, as well as a comparative analysis of the con-cept of the term «tender» in the current legislative acts of the United States of America, the People’s Republic of China and Turkmenistan. This allowed the authors to identify potential areas for reforming the Kazakh tender system by including the relevant concept of «tender» in the current legislation. Within the framework of the article, the main legal aspects of tender procedures were considered, which represent an opportunity through free and open contest to conclude a mutually beneficial contract for contractors, as well as types of tenders, their significance and features in the field of public procurement. The methodological basis of the re-search consists of general and special methods, such as formal logical, scientific analysis and synthesis, his-torical and legal and comparative legal methods. The results obtained from the research allowed the authors to formulate proposals and recommendations for improving the legislative framework to ensure the effective-ness and fairness of tender processes.